a Comprehensive and Inclusive Key Design for Smart Parking Solution Using the Three Validation Real Time Method - Rizkima Akbar Setiawan; Muhammad Fikri; Muhammad Nur Khawarizmi (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2025)
This study presents an innovative smart parking system known as SM Park, which utilizes the Three Validation Real-Time (3VR) method to provide accurate and efficient parking space monitoring. The system integrates multiple sensor technologies, including ultrasonic and Passive Infrared (PIR) sensors, along with computer vision, to detect the availability of parking slots in real-time. By leveraging the Internet of Things (IoT) and Artificial Intelligence (AI), SM Park enables users to reserve parking spaces in advance via its website, thus minimizing wait times and improving the overall efficiency of parking. The development process followed a prototype methodology, which allowed for rapid prototyping, feedback collection, and iterative design enhancements. The system's performance was evaluated through various stages, including literature review, system design, prototype development, and sensor integration. The system design eliminates the need for external devices such as RFID tags or mobile applications, creating a more inclusive parking solution. This paper outlines the design and architecture of the SM Park system, its technical components, and its potential for addressing key challenges in urban parking management, such as congestion, carbon emissions, and inefficient space utilization.